Small RNAs in eucaryotes: new clues for amplifying microRNA benefits - Bernardetta Ledda; Laura Ottaggio; Alberto Izzotti; Samir G. Sukkar; Mariangela Miele (Cell & Bioscience, 2020)
Abstract miRNAs, the smallest nucleotide molecules able to regulate gene expression at post transcriptional level, are found in both animals and plants being involved in fundamental processes for growth and development of living organisms. The number of miRNAs has been hypothesized to increase when some organisms specialized the process of mastication and grinding of food. Further to the vertical transmission, miRNAs can undergo horizontal transmission among different species, in particular between plants and animals. In the last years, an increasing number of studies reported that miRNA passage occurs through feeding, and that in animals, plant miRNAs can survive the gastro intestinal digestion and transferred by blood into host cells, where they can exert their functions modulating gene expression. The present review reports studies on miRNAs during evolution, with particular focus on biogenesis and mechanisms regulating their stability in plants and animals. The different biogenesis and post biogenesis modifications allow to discriminate miRNAs of plant origin from those of animal origin, and make it possible to better clarify the controversial question on whether a possible cross-kingdom miRNA transfer through food does exist. The majority of human medicines and supplements derive from plants and a regular consumption of plant food is suggested for their beneficial effects in the prevention of metabolic diseases, cancers, and dietary related disorders. So far, these beneficial effects have been generally attributed to the content of secondary metabolites, whereas mechanisms regarding other components remain unclear. Therefore, in light of the above reported studies miRNAs could result another component for the medical properties of plants. miRNAs have been mainly studied in mammals characterizing their sequences and molecular targets as available in public databases. The herein presented studies provide evidences that miRNA situation is much more complex than the static situation reported in databases. Indeed, miRNAs may have redundant activities, variable sequences, different methods of biogenesis, and may be differently influenced by external and environmental factors. In-depth knowledge of mechanisms of synthesis, regulation and transfer of plant miRNAs to other species can open new frontiers in the therapy of many human diseases, including cancer.